Narratives of resistance: Women’s defiance against gender oppression in Bonnie Garmus’ novel “Lessons in Chemistry” - Salwa Felisa Syafitri; Zhyldyz Tunguchbaevna Takenova (Researcher and Lecturer Society, 2025)
This article examines the multifaceted nature of women’s resistance to gender oppression as depicted in Bonnie Garmus’ novel “Lessons in Chemistry”. Through a qualitative feminist literary criticism approach, the study analyzes the protagonist Elizabeth Zott’s journey, highlighting her defiance against patriarchal norms in 1950s in America. Drawing on Simone De Beauvoir’s existentialist feminist theory and James C. Scott’s concepts of open and close resistance, the research uncovers how Elizabeth’s actions-ranging from public advocacy on her television show to private assertions of identity-challenge both overt and subtle forms of societal control. The findings reveal that resistance in the novel is both individual and collective, manifesting as visible protest and everyday acts of empowerment. By foregrounding these diverse strategies, the article demonstrates how literature can reflect and inspire ongoing struggles for gender equality, positioning resistance as a dynamic force that redefines women’s roles and catalyzes social change. Therefore, such studies on different literatures are recommended to conduct to ensure the writing quality and present moral values which are beneficial to adapt by the readers.